Sensor based on a non-ideal heterojunction to indicate X-ray images - Smyntyna, V.A.; Borschak, V.A.; Kutalova, M.I.; Zatovskaya, N.P.; Balaban, A.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The sensor of optical image on the basis of non-ideal heterojunctions are investigated in detail. In this work, the opportunity to obtain the image in X-rays was investigated. It is established that investigated sensor is sensitive to soft X-ray radiation. Memory and accumulation of a signal at a room temperature, which is characteristic of the sensor at registration of images in visible light, take place for the images obtained in X-ray range, too, which makes it possible to apply such sensor in medicine and crystallography.